Sound, Vision, and Embodied Performativity in Beyoncé Knowles’ Visual Album Lemonade (2016) - Johanna Hartmann (European Journal of American Studies)
In 2016, Beyoncé published Lemonade, a work of art that exists in various manifestations: as a music album that includes twelve songs, as live performances (including her world tour and her appearance at the Superbowl halftime show), and as a “visual album,” an art film that consists of the music video clips for each individual song and visually and auditorily complex “chapters” which feature the poetry by Warsan Shire. This article focuses on the visual album as intermedial artwork that can be described as a soundscape in which the intermedial constellations fulfill a number of functions: Firstly, intermedial references are a means of cohesion that are responsible for the unified character of the visual album. Secondly, intermedial references result in a transcultural signature of the artwork. Thirdly, through intermedial references Beyoncé locates Lemonade within the cultural history of the United States and American music history in particular. Finally, intermediality acquires cultural-critical functions which in particular pertain to race relations and structural forms of discrimination against people of color in contemporary America.